Window Frame Design Optimization Analysis Based on Hygrothermal Performance and the Level(s) Framework - Konstantin Verichev; Carmen Díaz-López; Andrés García-Ruíz; Francisca Valdenegro (Buildings)
This study investigates the hygrothermal performance of window frames to assess their capacity to prevent surface condensation—a critical factor for indoor air quality and building durability, particularly in humid climates. Driven by the practical need to replace existing aluminum frames with more sustainable alternatives, the research evaluates standard aluminum frames against modified timber frames designed to replicate the aluminum geometry. Using daily temperature and humidity data from Valdivia, Chile (2023)—a city with a temperate oceanic and humid climate—interior surface temperatures were simulated with HTflux software and compared against dew point values over a relative humidity (RH) range from 40% to 80%. A novel methodology is proposed for verifying the hygrothermal behavior of window frames based on annual performance analysis and highlighting the need to optimize window design according to specific local climate conditions. The results indicate that modified timber frames exhibited consistently lower average interior surface temperatures (by 1.2 °C) and a significantly higher risk of surface condensation compared to aluminum frames, particularly at typical comfort-level indoor humidity conditions (e.g., 167 vs. 100 condensation days at 50% RH). While both materials presented a high risk of condensation under extreme humidity conditions (80% RH), timber frames showed potentially greater severity of condensation. These findings underscore that the proposed timber frame modification is not hygrothermally adequate without strict control of indoor humidity. Anchored in the Level(s) framework, the study emphasizes the critical influence of geometric design on material performance and advocates for holistic, sustainable construction practices that balance energy efficiency, environmental impact, and occupant comfort. It highlights the need for integrated design solutions and effective moisture management to ensure building resilience in humid environments.